1989
DOI: 10.1016/0035-9203(89)90666-4
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus infections in humans and commensal rodents in Singapore

Abstract: To determine the extent of hantavirus infection in Singapore, serological studies using the indirect immunofluorescent antibody (IFA) test were conducted on commensal rodents and on human patients in 4 diagnostic groups. Virus isolation using a Vero E6 cell line was performed on hantaviral antigen-positive rodent lung tissue. Of 142 rodents and 3 insectivores studied, 37 (26%) were seropositive for IFA. Rattus norvegicus was the predominant species captured, with the highest species-specific seropositive rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Sin Nombre [SNV],Andes) are associated with pulmonary syndrome (hantavirus pulmonary syndrome [HPS]) [1]. In Southeast Asia, evidence of hantavirus infections have been reported from Korea, the Philippines, Singapore and Thailand [2][3][4][5]. In Indonesia, a serological study indicated the presence of a Seoul-like virus in wild rats [6].…”
Section: Serological Evidence Of Human Hantavirus Infections In Indonmentioning
confidence: 99%
“…Sin Nombre [SNV],Andes) are associated with pulmonary syndrome (hantavirus pulmonary syndrome [HPS]) [1]. In Southeast Asia, evidence of hantavirus infections have been reported from Korea, the Philippines, Singapore and Thailand [2][3][4][5]. In Indonesia, a serological study indicated the presence of a Seoul-like virus in wild rats [6].…”
Section: Serological Evidence Of Human Hantavirus Infections In Indonmentioning
confidence: 99%
“…In the late 80's in Singapore, Wong and co-workers found evidence of hantavirus infections in both rodents and humans and one hantavirus strain (R36) was isolated from R. norvegicus [21]. They also analyzed the seroprevalence in patients and found that 8.3% of Dengue Hemorrhagic Fever (DHF) suspects were seropositive to hantaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…The 2 earliest documented hantavirus infections in Peru were 2 SEOV HFRS case-patients confirmed by reverse transcription PCR, but both case-patients had fatal HFRS with HCPS ( 9 ), thus further blurring the boundaries between the 2 syndromes. In Southeast Asia, where the wild rat was and is the major reservoir for pathogenic hantaviruses, HFRS with liver involvement, imitating virus hepatitis, was moreover proposed as a new clinical entity ( 10 ). …”
mentioning
confidence: 99%